Granular cell odontogenic tumor: report of a rare case and a review of literature - Milad Etemadi Sh; Sayed Mohammad Razavi; Olia Ghazavi; Mohammad Hossein Nikbakht (BMC, 2022)
Abstract Background Granular cell odontogenic tumor (GCOT) is a rare neoplasm with about 45 cases reported in the literature. It usually occurs in the posterior mandible of middle-aged women. Case presentation We report a case of asymptomatic GCOT in the posterior mandible of a 28 years old female and provide a literature review of GCOT cases. Some unusual features such as root resorption, displacement of inferior tooth canal, and multilocular appearance were considerable in this case. Conclusions Complete surgical excision of the lesion was beneficial for the patient.